Correlation between Motivation and Professional Identity of Medical Students of Universitas Swadaya Gunung Jati, Cirebon, Indonesia - Mustopa, Mega Silvia Maulidia; Permatasari, Tissa Octavira; Sulistiyana, Catur Setya (GHMJ (Global Health Management Journal), 2025)
Background: Professional identity plays an important role for doctors in their practice. The important role of professional identity in medical education, namely learning the professionalism of doctors and being responsible for the duties of being a student and the rules that make it more responsible to patients. Professional identity is influenced by external and internal factors, one of which is motivation which plays an important role in medical education can foster creativity which makes the learning process a transformational experience that is important for the development of a strong professional identity. Objective: To determine the relationship between motivation and professional identity of students of the Faculty of Medicine, Universitas Swadaya Gunung Jati, Cirebon, Indonesia. Aims: To determine the relationship between motivation and professional identity of students of the Faculty of Medicine, Universitas Swadaya Gunung Jati, Cirebon, Indonesia. Methods: This research is an analytic observational study with a cross-sectional approach. Respondents were selected through Stratified Random Sampling technique, resulting in 295 respondents consisting of undergraduate and professional students. The study used primary data using the Academic Motivation Scale (AMS) questionnaire and Professional Identity with Spearman analysis. Results: This study involved 295 medical students (64.4% female and 35.6% male) from various academic stages, including undergraduate semesters 2, 4, 6, 8, and professional (clinical) phases from 2018 to 2019. Across all groups, most students had a good level of motivation (52.4-67.9%) and a high or very high professional identity. Spearman correlation analysis showed a significant positive relationship between motivation and professional identity (p= 0.000, r= 0.333). Conclusion: There is a significant positive relationship between motivation and professional identity.